U.S. Medical Student Attitudes Regarding Abortion Before and After Their OB/GYN Clerkship [25B]. (May 2016) - Peterson, Ashley T.; Kelly, Jeannie; Ferzandi, Tanaz R.
Abstract : INTRODUCTION: The continued safe, legal practice of abortion in the United States relies on future providers' willingness to provide care. We sought to determine medical student attitudes regarding abortion service provision before and after completing the OB/GYN clerkship. METHODS: Students were invited to complete a survey regarding abortion exposure and attitudes before their clerkship. A follow-up survey was sent to participants after their clerkship. The McNemar, Wilcoxon signed-rank and Wilcoxon rank sum tests were used for statistical analysis. RESULTS: 255 students completed the post-clerkship survey (64.7% response rate). 72.4% did not spend time with an abortion provider. 77.7% of students exposed to abortion care reported feeling more comfortable discussing abortion with patients, more than 2.5 times more likely than their peers ( P <.0001). Students were more likely to report changing their beliefs after shadowing abortion providers (18% versus 6%, P <.01). When exposed to abortion care, students were significantly more likely to report wanting to provide abortion care (Z=−3.786, P <.001), feel comfortable referring patients for abortion (Z=−2.64, P <.01), and believe an abortion curriculum is essential (Z=−3.79, P <.001). Students exposed to abortion care were more likely to express newfound interest in pursuing an OB/GYN residency after their clerkship ( P =.04, two-sided McNemar test). CONCLUSION: When exposed to abortion care, students are more likely to report comfort referring and providing such services in the future. The OB/GYN clerkship is an opportune time to educate students regarding abortion provision in order to ensure patients' continued access to care.